Outcomes of Patients with Tendinous Mallet Finger Injury Managed with DIPJ Extension Splinting vs Axial Pinning - Roel Gabriel Rabino; Raymar Sibonga (Philippine Journal of Orthopaedics)
Background: Mallet finger, a common finger injury, results from damage to the distal extensor tendon, causing a flexion deformity at the distal interphalangeal joint. While conservative treatment with splinting is often effective, surgical intervention using Kirschner wire fixation may be necessary for complex cases or non-compliant patients. Objective: This study compared the outcomes of two treatments for tendinous mallet finger: splinting and pinning. Researchers analyzed patient demographics, distal interphalangeal joint range of motion, clinical outcomes, and complication rates between the two groups.